2013
DOI: 10.1055/s-0033-1348473
|View full text |Cite
|
Sign up to set email alerts
|

DNA Viral Infections Complicating Lung Transplantation

Abstract: DNA viruses with potential to cause complications after lung transplantation include the human Herpesviridae family consisting of cytomegalovirus (CMV), herpes simplex virus 1 and 2 (HSV-1, -2), varicella-zoster virus (VZV), human herpesvirus 6, 7, and 8 (HHV-6, -7, -8), and Epstein-Barr virus (EBV); the Polyomaviridae family consisting of BK virus and JC virus; and the Adenoviridae family consisting of more than 50 adenovirus subtypes. This is a diverse group of viruses with equally diverse immediate and long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 356 publications
(756 reference statements)
0
12
0
1
Order By: Relevance
“…Long-term lung transplant outcomes have been linked to prior infection with several other viruses (1, 2, 4). While our subjects were sampled at relatively early time points (median 5 months post-transplant), early post-transplant colonization with other microbial agents has been associated with BOS at later time points (34, 35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-term lung transplant outcomes have been linked to prior infection with several other viruses (1, 2, 4). While our subjects were sampled at relatively early time points (median 5 months post-transplant), early post-transplant colonization with other microbial agents has been associated with BOS at later time points (34, 35).…”
Section: Discussionmentioning
confidence: 99%
“…For the case of lung transplantation, viral infection is a major complicating factor impacting graft survival rates (14). Respiratory infections with known viruses can cause direct lung injury or increase risk of graft failure, as in the case of cytomegalovirus and community acquired respiratory viruses (1, 5).…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of adenoviremia has been reported to be less than 10% of adult patients after kidney, heart, or liver transplantation; although the symptoms of HAdV infection are usually mild, and invasive infection does not correlate with organ rejection (157), severe and even fatal courses have also been described (158,159). Studies in patients undergoing lung transplantation showed that pulmonary infection with HAdV can correlate with significantly elevated rates of rejection, bronchiolitis obliterans, and mortality (160)(161)(162). In line with the epidemiology of HAdV infections, detection of this virus appears to be more common in pediatric SOT recipients (155,163), with reported rates of HAdV infection ranging from 3.5% to 38% after liver transplantation (164,165), from 7% to 50% after lung and heart transplantation (166)(167)(168), and from 4% to 57% after intestinal or multivisceral transplantation (169,170).…”
Section: Incidence Of Hadv Infections In Immunocompromised Adult and mentioning
confidence: 99%
“…159,164 The immune response to EBV infection is mediated by NK cells and cytotoxic CD4 and CD8 T lymphocytes. 150,165 With anti-T cell immunosuppression after transplant, EBV-infected B lymphocytes can proliferate with impunity. The polyclonal proliferation may transform to monoclonal proliferation that develops into a lymphoma.…”
Section: Epstein-barr Virus Epidemiology and Prevalencementioning
confidence: 99%